2001
DOI: 10.2136/sssaj2001.652527x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variability in Palustrine Wetlands

Abstract: Wetlands are complex ecosystems having considerable spatial variability. Understanding soil spatial relationships in wetlands is difficult because of the number of factors that affect soil properties. We established a nested sampling design within five small, forested and scrub‐shrub palustrine wetlands in Virginia to examine soil spatial variability within and among sites. Sampling was based on relative elevation intervals within each wetland and soil depth within each sampling unit. Soils were analyzed to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 24 publications
1
11
1
1
Order By: Relevance
“…A lower stock variability by level was observed in the Alocrisols-Neoluvisols compared with the Colluviosols-Fluviosols (Fig. 3) and confirmed the high spatial variability of soil properties in these locations [12,23,30,41].…”
Section: Effects Of Soil Type and Hydromorphysupporting
confidence: 68%
“…A lower stock variability by level was observed in the Alocrisols-Neoluvisols compared with the Colluviosols-Fluviosols (Fig. 3) and confirmed the high spatial variability of soil properties in these locations [12,23,30,41].…”
Section: Effects Of Soil Type and Hydromorphysupporting
confidence: 68%
“…2 L) was placed into a paper bag. Prior studies have found no significant difference in soil properties (organic C, N, pH, Ca and Mg) within small (0.25–0.35 ha) palustrine wetland sites among samples taken at the same depth (Stolt et al ., 2001). Therefore, we restricted soil sampling to the root zone at a single depth (5–10 cm below surface) within and across sites (Binkley & Vitousek, 1989).…”
Section: Methodsmentioning
confidence: 90%
“…Wetland soil property heterogeneity is linked with differences in parent material, elevation, topography, erosional or depositional environment, vegetation, pedogenic effects and hydrology (Stolt et al, 2001). Turloughs are likely to exhibit a high degree of soil property heterogeneity as the turlough landform is recognised as highly variable with regards to size (\0.1 to [3 km 2 ), depth, topography, groundwater connections and inundation patterns (Sheehy Skeffington et al, 2006).…”
Section: Introductionmentioning
confidence: 99%